An Assessment of Pseudo-Operational Ground-Based Light Detection and Ranging Sensors to Determine the Boundary-Layer Structure in the Coastal Atmosphere - Conor Milroy; Giovanni Martucci; Simone Lolli; Sophie Loaec; Laurent Sauvage; Irène Xueref-Remy; Jošt V. Lavrič; Philippe Ciais; Dietrich G. Feist; Gionata Biavati; Colin D. O'Dowd (Advances in Meteorology)
Twenty-one cases of boundary-layer structure were retrieved by three co-located remote sensors, One LIDAR and two ceilometers at the coastal site of Mace Head, Ireland. Data were collected during the ICOS field campaign held at the GAW Atmospheric Station of Mace Head, Ireland, from 8th to 28th of June, 2009. The study is a two-step investigation of the BL structure based on (i) the intercomparison of the backscatter profiles from the three laser sensors, namely the Leosphere ALS300 LIDAR, the Vaisala CL31 ceilometer and the Jenoptik CHM15K ceilometer; (ii) and the comparison of the backscatter profiles with twenty-three radiosoundings performed during the period from the 8th to the 15th of June, 2009. The sensor-independent Temporal Height-Tracking algorithm was applied to the backscatter profiles as retrieved by each instrument to determine the decoupled structure of the BL over Mace Head. The LIDAR and ceilometers-retrieved BL heights were compared to the radiosoundings temperature profiles. The comparison between the remote and the in-situ data proved the existence of the inherent link between temperature and aerosol backscatter profiles and opened at future studies focusing on the further assessment of LIDAR-ceilometer comparison.